Prior participation in the strange situation and overstress jointly facilitate disorganized behaviours: implications for theory, research and practice. Issue 3 (3rd May 2016) - Granqvist, Pehr; Hesse, Erik; Fransson, Mari; Main, Mary; Hagekull, Berit; Bohlin, Gunilla
ABSTRACT: We seek to understand why a relatively high percentage (39%; vs the meta-analytic average, 15–18%) of disorganized/disoriented (D) classifications has accrued in the low-risk Uppsala Longitudinal Study (ULS) study, using experienced D coders. Prior research indicates that D behaviours do not always indicate attachment disorganization stemming from a history of frightening caregiving. We examined the role of two other presumed factors: participation in a previous strange situation and overstress. Our findings indicate that both factors were highly prevalent in the ULS sample and that they jointly predicted higher rates of D. First, participation in a previous strange situation was associated with significantly higher distress displays during the second visit than occurred among previously untested children, suggesting that prior participation in the strange situation had a sensitizing effect on child distress during the second visit. Second, unless separations were cut short in lieu of high distress during the second visit, re-tested children were disproportionately likely (ca 60%) to be classified D. We argue that these findings have important implications for theory, research, and practice. In particular, we conclude that practitioners must refrain from misattributing the appearance of any D behaviors observed to a history of maltreatment.